Resource exchange in urban governance: on the means that matter - Poppelaars, Caelesta (2007)
An explanatory framework based on the classic resource dependency perspective is used to explain a broad variety of urban government-interest group interactions that are not fully explained by current urban governance theories. A case study of Dutch urban immigrant integration shows that one must combine considerations of information and intermediation capacity to explain why Dutch urban governments interact with immigrant organizations, in addition to common findings about institutional heritage. Their information and intermediation capacity allows local governments to get in touch quickly with immigrant groups during periods that potentially threaten the social order and public safety and creates incentives to maintain grants and keep in touch, whereas contributions of such groups to effective implementation are at least doubted. - Reproduced.
Keywords: Urban development